Serum albumin and risks of hospitalization and death: Findings from the Atherosclerosis Risk in Communities study. Issue 10 (23rd July 2021) - Shannon, Colleen M.; Ballew, Shoshana H.; Daya, Natalie; Zhou, Linda; Chang, Alex R.; Sang, Yingying; Coresh, Josef; Selvin, Elizabeth; Grams, Morgan E.
Abstract: Objectives: To determine whether lower serum albumin in community‐dwelling, older adults is associated with increased risk of hospitalization and death independent of pre‐existing disease. Design: Prospective cohort study of participants in the fifth visit of the Atherosclerosis Risk in Communities (ARIC) study. Baseline data were collected from 2011 to 2013. Follow‐up was available to December 31, 2017. Replication was performed in Geisinger, a health system in rural Pennsylvania. Setting: For ARIC, four US communities: Washington County, Maryland; Forsyth County, North Carolina; Jackson, Mississippi; and suburbs of Minneapolis, Minnesota. Participants: A total of 4947 community‐dwelling men and women aged 66 to 90 years. Exposure: Serum albumin. Main Outcomes: Incident all‐cause hospitalization and death. Results: Among the 4947 participants, mean age was 75.5 years (SD: 5.12) and mean baseline serum albumin concentration was 4.05 g/dL (SD: 0.30). Over a median follow‐up period of 4.42 years (interquartile interval: 4.16–5.05), 553 participants (11.2%) died and 2457 participants (49.7%) were hospitalized at least once. The total number of hospitalizations was 5725. In analyses adjusted for demographics and numerous clinical characteristics, including tobacco use, obesity, frailty, cardiovascular disease, kidney disease, diabetes C‐reactive protein (CRP), cognitive status, alcohol use, medication use, respiratory disease, and systolic blood pressure, 1 g/dL lower baseline serum albumin concentration was associated with higher risk of both hospitalization (incidence rate ratio [IRR]: 1.58; 95% confidence interval [CI]: 1.36–1.82; p  < 0.001) and death (hazard ratio [HR]: 1.67; 95% CI: 1.24–2.24; p  < 0.001). Associations were weaker with older age but not different by frailty status or level of high‐sensitivity CRP. Associations between serum albumin, hospitalizations, and death were also similar in a real‐world cohort of primary care patients. Conclusions: Lower baseline serum albumin was significantly associated with increased risk of both all‐cause hospitalization and death, independent of pre‐existing disease. Older adults with low serum albumin should be considered a high‐risk population and targeted for interventions to reduce the risk of adverse outcomes.